(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Airway management remains a fundamental component of anaesthetic practice. Video laryngoscopes have emerged as valuable tools for improving glottic visualisation and facilitating endotracheal intubation compared to conventional laryngoscopes. The present study evaluated and compared the intubation characteristics of video laryngoscope and McCoy laryngoscope in patients undergoing general anaesthesia. Methods: This prospective comparative study was conducted in the Department of Anaesthesiology, Gandhi Medical College and Associated Hospitals, Bhopal, among 100 patients aged 18–60 years belonging to ASA physical status I and II undergoing elective surgeries under general anaesthesia. Patients were randomly allocated into two groups: Group M (McCoy laryngoscope) and Group V (Video laryngoscope), with 50 patients in each group. Parameters assessed included intubation time, number of attempts, Intubation Difficulty Score (IDS), Cormack–Lehane grading, haemodynamic responses, oxygen saturation, and complications. Statistical analysis was performed using appropriate statistical tests. Results: Video laryngoscope demonstrated significantly better glottic visualisation with lower Cormack–Lehane grades and lower IDS scores compared to McCoy laryngoscope. The first-attempt intubation success rate was higher in the video laryngoscope group. Mean intubation time was significantly shorter in Group V compared to Group M (p<0.05). Haemodynamic responses including pulse rate and blood pressure changes were comparatively lower in the video laryngoscope group following intubation. Complication rates were minimal and comparable between both groups. Conclusion: Video laryngoscope provided superior glottic visualisation, easier intubation, improved first-pass success rate, and better haemodynamic stability compared to McCoy laryngoscope in patients undergoing general anaesthesia. Video laryngoscopy may therefore be considered a preferable technique for routine endotracheal intubation.